A Case Study on the Sri Lankan English Language Learner in the field of Creative Arts - Niroshani, B.A.Ajantha (Future Science / FSH-PH Publications, 2021)
This article reports the findings of a study that investigated the attitudes of creative arts undergraduates and the attitudes and perception of English as a second language (ESL) teachers from different faculties in three Sri Lankan universities about the motivation and proficiency of their students. Employing a qualitative approach in which a 20-item 6- point Likert scale questionnaire and eight (8) item online questionnaire served as the instuments respectively for randomly selected 25 students and the 10 ESL teachers. The results of the study revealed that the undergraduates were aware of the role played by the English language in terms of the potential utility,importance of learning and the potential impact on their future employment.According to the data analysis,the undergraduates in the faculties of medicine and science are motivated than their counterparts in the faculty of creative arts.Differenciations were observerd in terms of independent thinking, enthusiasm for classroom tasks and critical thinking between the same.